PERBANDINGAN SENSITIVITAS ETIS ANTARA MAHASISWA AKUNTANSI PRIA DAN WANITA SERTA MAHASISWA AKUNTANSI DAN MANAJEMEN (Studi Empirik Pada Perguruan Tinggi Di Semarang) - Andi Kartika (Dinamika Akuntansi Keuangan dan Perbankan, 2013)
This study will analyze the differences in ethical sensitivity of students in Semarang. The goal is to determine differences in the activity and behavior of the students. The population in this study were students of accounting and management at private universities in Semarang. In this study the researchers used the criteria to get closer to the subject matter. The criteria used in this study were students who were third semester to semester end. Results of this study indicate that there is no difference between unethical behavior and student management accounting students. There is no difference between unethical behavior male and female accounting students. Students are more tolerant of unethical behavior will be more cynical.Keywords: Ethical Sensitivity, cynical attitude.